Maternal Body Mass Index and Risk of Congenital Heart Defects in Infants: A Dose-Response Meta-Analysis. (7th July 2019) - Liu, Xuezhen; Ding, Guoyong; Yang, Weili; Feng, Xia; Li, Yuejin; Liu, Huamin; Zhang, Qianqian; Ji, Long; Li, Dong
Abstract : Objective . The exact shape of the dose-response relationship between maternal body mass index (BMI) and the risk of congenital heart defects (CHDs) in infants has not been clearly defined yet. This study aims to further clarify the relationship between maternal obesity and the risk of CHDs in infants by an overall and dose-response meta-analysis. Methods . PubMed, Embase, and Web of Science databases were searched to identify all related studies. The studies were limited to human cohort or case-control studies in English language. Random-effect models and dose-response meta-analysis were used to synthesize the results. Heterogeneity, subgroup analysis, sensitivity analysis, and publication bias were also assessed. Results . Nineteen studies with 2, 416, 546 participants were included in our meta-analysis. Compared with the mothers with normal weight, the pooled relative risks (RRs) of infants with CHDs were 1.08 (95% CI=1.03-1.13) in overweight and 1.23 (95% CI=1.17-1.29) in obese mothers. According to the findings from the linear meta-analysis, we observed an increased risk of infants with CHDs (RR=1.07, 95% CI=1.06-1.08) for each 5 kg/m 2 increase in maternal BMI. A nonlinear relationship between maternal BMI and risk of infants with CHDs was also found ( p =0.012). Conclusion . The results from our meta-analysis indicate that increased maternal BMI is related to increased risk of CHDs in infants.